(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2021)
This article, starting from a recent event that is under the inspection of the Italian Data protection authority, examines the protection of the mother’s personal data with respect to the public interests to the knowledge of the identity of the mother itself and the practice.